2020
DOI: 10.1088/1742-6596/1660/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Biological Activity of Mixed Ligand Metal Salts Complexes with Various Ligands

Abstract: Metal (III) and (II) coordination compounds of o- phenylenediamine, oxalic acid dihydrate and 8-hydroxyquinoline were synthesized for mixed ligand complexes and characterized using FT-IR, UV-Vis and mass spectra, atomic absorption, elemental analysis, electric conductance and magnetic susceptibility measurements. In addition, thermal behavior (TGA) of the metal complexes (1-6) showed good agreement with the formula suggested from the analytical data. The stoichiometric reaction between the metal (III) and (II)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Obaid et al reported that the best ligand concentration for extracting metal ions from water by cloud point extraction (CPE) was 55 × 10 -4 mol L -1 . At a higher concentration (excess of LH 2 ), competition with a complexing agent (Triton X-114) reduces the metal ion concentration in complexes and decreases absorbance [24].…”
Section: Effect Of Ligand Amountmentioning
confidence: 99%
“…Obaid et al reported that the best ligand concentration for extracting metal ions from water by cloud point extraction (CPE) was 55 × 10 -4 mol L -1 . At a higher concentration (excess of LH 2 ), competition with a complexing agent (Triton X-114) reduces the metal ion concentration in complexes and decreases absorbance [24].…”
Section: Effect Of Ligand Amountmentioning
confidence: 99%
“…We observed that the remaining complexes are metal oxides, and the remaining ligand is carbon. In addition, the DSC curve is used to determined exothermic, or endothermic and amount of heat [34][35][36]. The results of thermal studies of the ligand and its complexes are represented in Table 5, Scheme 2 and Figures 3-5.…”
Section: Thermal Studiesmentioning
confidence: 99%
“…(Two negative for Gram stain and two positive for Gram stain, the compound is effective against positive stain bacteria. Staphylococcus aurous and Streptococcus pneumonia) are effective against Escherichia coil negative bacteria only at 200 ml / mg [26][27] egt. All Antibacterial activities of the prepared compounds in Fig.…”
Section: Biological Activitymentioning
confidence: 99%